ANALISIS KESULITAN BELAJAR SISWA KELAS V PADA MATA PELAJARAN MATEMATIKA DI SEKOLAH DASAR - Alia Fatimah; Jesi Alexander Alim (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2023)
This study aims to determine the difficulties in learning mathematics experienced by students at SDN 110 Pekanbaru, determine the causes, and efforts to overcome difficulties in learning mathematics. The type of research used is qualitative research. Data collection methods used are observation and interviews. The results showed that: (1) students had difficulty understanding the concept (2) factors that caused students to experience difficulties in learning mathematics, which are internal factors (lack of understanding of mathematics, lack of interest in student learning and different levels of student IQ) and external factors (lack of teacher variation in learning). (3) efforts to overcome difficulties in learning mathematics. It is hoped that the teacher can overcome the difficulties in learning mathematics experienced by students